EFFECT OF LENGTH EXPOSURE AND TYPES OF VOICE ON CORN SEEDS (Zea Mays) VIABILITY AND EARLY GROWTH - Jasmi; Maja, Ibnu; Agustinur (Jurnal Online Pertanian Tropik, 2022)
Seed quality includes three aspects, namely genetic quality, physical quality and physiological quality. Physiological quality is an aspect of seed quality as indicated by seed viability and vigor. This study aims to analyze the effect of different types of sound exposure on viability and early growth of corn seeds, and to analyze the effect of long exposure to sound on viability and early growth of maize seeds. The research was carried out in the laboratory of the Faculty of Agriculture, Teuku Umar University. on September 20 - October 19, 2019. This study used a Split Plot with the main plot type of sound exposure consisting of four levels, and the main sub-plot, namely the length of sound exposure consisting of three levels. Observed parameters; germination rate, growth speed, synchronous growth (KST), stomata openings. Based on the research results, the best germination rate, growth rate, growth impregnability, leaf width, and stomatal openings were found in the Murrotal Al-Quran exposure. In the long exposure to sound treatment, it showed that the length of exposure to sound had no significant effect on germination, growth speed, growth impregnability, leaf width of maize plants, and stomata opening of maize plants.